Teachers’ Awareness in Artificial Intelligence and Digital Competence in the Workplace - Karen A Manaig; Alberto D Yazon; Chester Alexus C Buama; Ruel T Bonganciso (Research Synergy Foundation, 2025)
This study explores how artificial intelligence (AI) influences education, particularly in teaching, learning, and assessment. While AI offers benefits such as personalized learning, automation, and data-driven feedback, it also brings challenges such as data privacy, teacher adaptation, and equity concerns. This research examines the link between teachers’ awareness of AI and their digital competence in the workplace. Using a descriptive correlational design, data were collected via an online survey from 144 public basic education teachers in Laguna, Philippines. The study employed validated tools: the AI Awareness Scale and the Digital Competence Questionnaire. Results showed that only one factor—attendance at AI or ICT-related training—significantly influenced AI awareness (p = .044). Thus, the hypothesis was partially accepted, as the other demographic attributes showed no significant differences. However, a notable finding is the rejection of the hypothesis that no significant relationship exists between AI awareness and digital competence, suggesting a meaningful connection between the two. This research provides new insights into a relatively unexplored area: how teachers’ understanding of AI correlates with their ability to effectively use digital tools. Although AI’s role in fields such as health care and technology is well studied, its educational impact, particularly on teachers’ preparedness, remains underrepresented.